Krzysztof Kieślowski and Ingmar Bergman – once again about a certain artistic relationship - Dąbrowski, Radosław (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Krzysztof Kieślowski and Ingmar Bergman belonged to different generations of film authors, but there was a certain artistic kinship between them. They were both interested in issues related to human existence, but their films also seem similar in terms of their aesthetic dimensions, in particular, their cinematographic style. Both directors also created films deriving from their private experience, often creating characters on screen who seem to be in some respect their alter egos. This articles deals with various similarities between the cinema of Kieślowski and Bergman.